Expressão gênica e proteica da cox-2 e c-Kit em neoplasias mamárias de cadelas - Salvador, Rosana da Cruz Lino [UNESP] (2014)
Mammary tumors is the most frequent neoplasm in bitches and its biological behavior is similar to those that occur in womens, making bitches an excellent model to comparative studies. Discovery of proteins with predictive value is important to determine specifi therapeutic targets for each tumor type. The aims of this study were to evaluate gene and protein expression of COX-2 and c-KIT in normal mammary glands, benign lesions and mammary carcinomas with and without metastasis to correlate then with clinical and epidemiological variables. To this, were used 124 bitches with mammary lesions and also 13 bitches with no history of mammary tumors. Four groups were formed: G1 = normal mammary glands; G2= benign lesions; G3= non-metastatic mammary carcinomas and G4= metastatic mammary carcinomas. Gene expression analysis was conducted by RT-qPCR method and protein expression was assessed by immunohistochemistry. Difference on transcripts COX-2 level was observed in normal mammary glands and metastatic carcinomas (p<0.05) when compared to other groups. In c-KIT evaluation no difference on transcripts level was observed among groups. The immunostaining for COX-2 and c-KIT among the four groups was significantly different (p=0.0002 and p=0.0003, respectively). High expression of c-KIT was observed mainly in normal mammary glands with a decrease in its expression to malignant tissues. The opposite was observed in COX-2 immunostaining and its expression increased in malignant samples. COX-2 can be a good prognosis and predictive marker in canine mammary tumors, however c-KIT cannot be used as an independent marker